The effects of treating the seedlings of a Strawberry (L. Fragaria Ananassa) plant with a Colchicine on its morphology Characteristics and the growth of its seedlings - Mahmoud, Yussof abedalrahman; Obaid, Iyad Assi; Ali, Nizar Suleiman; Shalahi, Star Abdullah (Journal of agricultural, environmental and veterinary sciences, 2019)
An experiment was conducted in the research station Horticulture and landscape gardening Dept./college of Agriculture university of Diyala for the period from 2016/12/15 up to 2017/7/1. Study of the effect of colchicine and its effect to deteted the effect on the Vegetative growth, stomata Characteristics of the Strawberry plant when treating its apical part by the Colchicine with concentrations of zero, 0.05, and 0.1%. The number of treatment times was (one treatment and two treatments). The results of experiment showed that the plants that treated with 0.1% Colchicine were Increased leaf area to (138.7 cm2), the content of Chlorophyll in the leaf to (51.450 SPAD), the wet weight of the leafs (3.033 gm), the dry weight of the Leave (0.550 g), the length of Stomata (26.75 µ), the width of the stomata (11.42 µ). when Compared with the control value of treatment, it found that the control value of treatment has more number of stomata with average (26 stomata.mm2). while with the treatment of 0.05 % concentration, On the other hand, when treating the Shoot tip of the plant tow times, it found that the plants have better leaf area (119.188 cm2), amount of Chlorophyll (47.222 SPAD), dry weight (0.558 g), length of stomata (25.16 µ), and the width of the stomata (10,49 µ), compared to single treatment. The double overlap between the concentration and the number of treatment times resulted in a significant increase in the area of paper area, chlorophyll content in leaves, leaf content of wet material, length of hole in treatment with 0.1% concentration, While the concentration of 0.1% and the treatment only once in the character and content of the leaves of the dry material and the width of the gaps of the paper as it reached 0.690 g and 11.62 on the relay.